Australian parents' willingness to use a rideshare vehicle to transport their unaccompanied children. (April 2022) - Koppel, Sjaan; Peiris, Sujanie; Zou, Xin; Wong, Chernyse W.R.; Logan, David B.
Highlights: Rideshare services have the potential to extend child occupants' mobility. Australian parents are mostly 'unwilling' to use a rideshare vehicle to transport their unaccompanied children. Willingness to use a rideshare vehicle to transport unaccompanied children was associated with previous use of a rideshare vehicle with their child. Willingness was also associated with optimism regarding technology, driving violations, and requiring the rideshare vehicle to have fewer route- or assurance-related features. Abstract: This study aimed to identify the key factors associated with Australian parents' willingness to use a rideshare vehicle to transport their unaccompanied child(ren). Six hundred and thirty-one participants completed an online survey (M = 39.2 years, SD = 10.5, Range = 18.0–70.0 years; Female: 63.4%). Most participants (62.1%) reported that they would 'never' use a rideshare vehicle to transport their unaccompanied child(ren). The results of a logistic regression model showed that participants': previous use of a rideshare vehicle with their child, annual mileage, propensity for technology adoption, aberrant driving behaviours, as well their requirements for vehicle features were significantly associated with their willingness to use a rideshare vehicle to transport their unaccompanied child, χ2(7) = 159.59, p < 0.001. Overall, the findings suggest that Australian parents are mostly 'unwilling' to use a rideshare vehicle to transport their unaccompanied children. Understanding the views of parents towards emerging transportation modes for their children is crucial for urban planning, traffic engineering, economic and social mobility and ultimately, on supporting safe modes of transportation.